ANALISIS PENGARUH PELAKSANAANPEMERIKSAAN PAJAK DAN PENERAPAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK BADAN PADA KPP DI WILAYAH KOTA BANDAR LAMPUNG - Indri Erani; Reva Meiliana (Jurnal Bisnis Darmajaya, 2016)
The purpose of this research is to empirically demonstrate the influence of the implementation of tax audit and tax penalties application on corporate tax payers compliance at KPP regional offices in Bandar Lampung. The variables in this research consisted of the dependent variable corporate taxpayers compliance (Y) and the independent of variables, tax audit (X1) and tax penalties (X2).The population of this research is functional tax officials and tax inspectors listed in KPP regional offices in Bandar Lampung as 48 tax employees. The sample was taken by purposive sampling method that was as 45 tax officials. Method of data collection was structured questionnaires, and method of analysis of this research is multiple regression. The validity test were performed using an analysis of product moment and calculations using SPSS version 20.The results of this research are that the implementation of tax audit and application, tax penalties have an effect on corporate taxpayers compliance at KPP regional offices in Bandar LampungKeywords:tax audit, tax penalties, corporate taxpayers compliance